(untitled) (Archives of Mechanics - Test, 2002)
The tensile behaviour of a rigid-plastic single crystal obeying Schmid’s law with isotropic hardening is investigated for an off-axis tensile test in one of its symmetry planes (plane single crystal). Identification of the active slip systems allows the determination of the plastic spin and the resulting evolution of the crystallographic directions. This results in the description of the tensile behaviour-stress and strain response, onset of instability - depending upon the initial orientation of the crystal and the hardening law.